Security on 802.11 Wireless LAN a Comprehensive Comparison - Wawan Indarto (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
Since the ratification of the IEEE 802.11b standard in 1999, wireless LANs have become more prevalent.Today, wireless LANs are widely deployed in places such as corporate office conference rooms, industrialwarehouses, Internet-ready classrooms, and even coffeehouses.These IEEE 802.11-based wireless LANs presentnew challenges for network administrators and information security administrators alike. Unlike the relativesimplicity of wired Ethernet deployments, 802.11-based wireless LANs broadcast radio-frequency (RF) data forthe client stations to hear.[2] This presents new and complex security issues that involve augmenting the 802.11standard.Keyword: IEEE 802.11, WLAN, Security